Vectors for Genetically-Encoded Tags for Electron Microscopy Contrast in Drosophila. Issue 1 (December 2016) - Tsui, Marco; Itoh, Anri; Amgad, Mohamed; Wang, Shao-Fang; Sasaki, Toshio
Abstract Background One of the most notable recent advances in electron microscopy (EM) was the development of genetically-encoded EM tags, including the fluorescent flavoprotein Mini-SOG (Mini-Singlet Oxygen Generator). Mini-SOG generates good EM contrast, thus providing a viable alternative to technically-demanding methods such as immuno-electron microcopy (immuno-EM). Based on the Mini-SOG technology, in this paper, we describe the construction, validation and optimization of a series of vectors which allow expression of Mini-SOG in theDrosophila melanogaster genetic model system. Findings We constructed a Mini-SOG tag that has been codon-optimized for expression inDrosophila (DMS tag) using PCR-mediated gene assembly. The photo-oxidation reaction triggered by DMS was then tested using these vectors inDrosophila cell lines. DMS tag did not affect the subcellular localization of the proteins we tested. More importantly, we demonstrated the utility of the DMS tag for EM inDrosophila by showing that it can produce robust photo-oxidation reactions in the presence of blue light and the substrate DAB; the resultant electron micrographs contain electron-dense regions corresponding to the protein of interest. The vectors we generated allow protein tagging at both termini, for constitutive and inducible protein expression, as well as the generation of transgenic lines by P-element transformation. Conclusions We demonstrated the feasibility of Mini-SOG tagging inDrosophila . The constructed vectors will no doubt be a useful molecular tool for genetic tagging to facilitate high-resolution localization of proteins inDrosophila by electron microscopy.